Brief Report: Hormonal Contraception Use and Cabotegravir Pharmacokinetics in HIV-Uninfected Women Enrolled in HPTN 077. (1st September 2020) - Blair, Cheríe S.; Li, Sue; Chau, Gordon; Cottle, Leslie; Richardson, Paul; Marzinke, Mark A.; Eshleman, Susan H.; Adeyeye, Adeola; Rinehart, Alex R.; Margolis, David; McCauley, Marybeth; Hendrix, Craig W.; et al.
Abstract : Objectives: To evaluate whether hormonal contraceptive use among cisgender women is associated with differences in pharmacokinetic (PK) parameters of a long-acting injectable formulation of the integrase strand transfer inhibitor, cabotegravir (CAB-LA). Setting: This is a secondary analysis of 85 cisgender women enrolled in HPTN 077, a phase 2a multicenter study that enrolled HIV-uninfected, low-risk individuals in Malawi, Brazil, South Africa, and the United States. Methods: Participants received 4-week daily oral cabotegravir lead-in, followed by CAB-LA 800 mg injection every 12 weeks (cohort 1) or 600 mg every 8 weeks (after 4-week initial interval between injections, cohort 2), over 41 weeks. Participants were followed 52–76 weeks subsequent to final injection. Generalized estimating equations and linear regression were used to evaluate differences in CAB-LA PK parameters (peak concentration, trough concentration, area under the curve, apparent terminal half-life, and time to lower limit of quantification) and self-reported hormonal contraceptive stratified by type (oral, injectable, implants, and other), controlling for body mass index and cohort. Results: Compared to women reporting no hormonal contraception (n = 6), oral contraceptive use (n = 18) was associated with lower CAB-LA peak concentration but was not associated with differences in other PK parameters. No other hormonal contraceptive type (injectable, implants, and other) was associated with significant differences in CAB-LA PK parameters. Conclusion: Although oral contraceptive use was associated with differences in CAB-LA peak concentration, no differences were observed in other PK parameters, suggesting that this association is not likely to be clinically significant. However, these data highlight the need for further research exploring potential drug–drug interactions between CAB-LA and hormonal contraceptives. Abstract : Supplemental Digital Content is Available in the Text.